Methodical concepts and assumptions underlying research methods for studies on the erratic raw material of the Polish Lowland. Geology versus archaeology - Chachlikowski, Piotr (Archaeopress Publishing Ltd, 2018)
Inadequate levels of identification of glacial resources of raw materials in the Polish Lowlands areas and unreliable geological determinations of the assortment and frequency of local Fennoscandian erratics have established the opinion among archaeologists of alleged shortages in appropriate petrologically differentiated material necessary for stone industry in glacial areas. The claim has been made that raw material shortages were supplemented by massive imports of exogenous rocks from areas of their natural deposits. Yet a long study undertaken by the author on the Lowland inventory of erratics has proved that they constituted an extremely abundant and lithologically diversified source of raw materials. In the study, relatively large numbers of boulders and pebbles have been examined, regardless of their so-called indicating usefulness and with their appropriate overall measurements parameters taken into consideration. The exceptional abundance of local glacial ‘deposits’ effectively balanced the deficit in imported rock raw material for the local stone worker and inhibited the demand for imports.
Keywords: archaeology; petroarchaeology; methods and methodology in archaeology; lithic raw material sourcing; geoarchaeology and lithic studies